IDENTIFICATION OF MISSED HYPERTENSION AND HYPERTENSIVE ARTERIOPATHY WITH HOME VERSUS AMBULATORY BLOOD PRESSURE MEASUREMENT IN PATIENTS WITH TIA OR MINOR STROKE. Issue 11 (9th October 2013) - Webb, Alastair; Li, Linxin; Simoni, Michela; Wilson, Michelle; Paul, Nicola; Tarassenko, Lionel; Rothwell, Peter
Abstract : Background: Hypertension is a major treatable cause of incident and recurrent stroke. However, it can be missed by one–off clinic measurements. Hypertension guidelines therefore currently recommend ambulatory monitoring (ABPM) prior to treatment in primary prevention. Given high rates of under–treatment of hypertension in secondary prevention after TIA and stroke, we compared Bluetooth home BP monitoring (HBPM) and ABPM in identifying hypertension missed at initial assessment, with validation against pre–morbid BP and markers of hypertensive arteriopathy. Methods: Consecutive patients recruited to the Oxford Vascular Study with TIA or minor stroke underwent HBPM (3 measurements, 3 times daily for 7 days) and ABPM at 1 month after presentation. Mean SBP was related to premorbid hypertension (defined as mean SBP>140 or mean DBP>90 based on all BP measurements during the previous 10 years in primary care or a formal diagnosis of hypertension in primary care) and markers of hypertensive arteriopathy (creatinine, aortic stiffness–pulse wave velocity–and leukoaraiosis on brain imaging). Results: Among 500 eligible patients, those with premorbid hypertension (n=307) were better identified (p<0.001) by mean SBP on HBPM than by mean awake SBP on ABPM (area under ROC curve: 0.73, 95%CI 0.67–0.78 vs 0.60, 0.54–0.65). This difference was also present for identification of patients (n=205) with mean pre–morbid BP>140/90 but no formal premorbid diagnosis of hypertension (0.77, 0.69–0.85 vs 0.57, 0.46–0.69), including those who were normotensive in the stroke clinic (0.84, 0.73–0.96 vs 0.64, 0.40–0.89). HBPM SBP was also more strongly associated than ABPM with creatinine (r=0.24, p<0.001 vs r=0.14, p=0.002), aortic stiffness (r=0.21, p=0.01 vs r=0.13, p=0.13) and moderate/severe leukoaraiosis (AUC: 0.61, 0.55–0.67 vs 0.49, 0.43–0.55). Conclusions: In patients with TIA or minor stroke, HBPM was more reliable than ABPM at identifying missed hypertension and hypertensive arteriopathy. Its use could significantly reduce the risk of recurrent stroke.